Stimuli-responsive hybrid materials: breathing in magnetic layered double hydroxides induced by a thermoresponsive molecule1. Issue 3 (16th March 2015) - Abellán, Gonzalo; Jordá, Jose Luis; Atienzar, Pedro; Varela, María; Jaafar, Miriam; Gómez-Herrero, Julio; Zamora, Félix; Ribera, Antonio; García, Hermenegildo; Coronado, Eugenio
<x xml:space="preserve">Abstract</x> A hybrid magnetic multilayer material consisting of CoAl–LDH ferromagnetic layers intercalated with thermoresponsive molecules diluted with a flexible surfactant has been obtained.